Ultrasound in obstetric anesthesia and critical care - Ranjana Khetarpal; Puneetpal Kaur; Anuradha Borle; Anjan Trikha (Wolters Kluwer Medknow Publications, 2020)
Ultrasound is a safe and inexpensive imaging modality, which can be used as a diagnostic and monitoring tool in anesthesiology, along with therapeutic management of emergency and critical illness scenarios. This current review considers an array of recent applications of ultrasound in obstetric anesthesia, encouraging its use as standard practice for diagnostic and therapeutic management. The rapid advancement of clinical applications of ultrasound in obstetric anesthesia needs an appraisal for its uses and limitations. This review presents ultrasound application under various scenarios such as difficult neuraxial blockade and airway management, gastric antrum assessment, difficult intravascular access, transverse abdominal plane block for pain management, lung ultrasound, and transthoracic echocardiography and assessment of intracranial hypertension and usage in emergency and critical care in obstetrics. Each application is presented with recent advances along with limitations to its use in clinical practice. Ultrasound is becoming a versatile tool nowadays for obstetric anesthesiologists for providing the best care possible.